Diagnostics of Low Pressure DC Glow Discharge Using Double Langmuir Probe - Ghimire, B.; Khanal, R.; Subedi, D.P. (Kathmandu University Journal of Science, Engineering and Technology, 2014)
This paper reports the result of electrical diagnostics of low pressure DC glow discharge using Langmuir double probe. The electron and ion distribution function at the probe sheath edges are considered to be Maxwellian so that the most important requirement of pre-sheath and sheath transitions are satisfied. The electrons and ions are assumed to penetrate the sheath region due to their large thermal velocities. Using the probe biasing technique, the discharge plasma parameters like electron temperature (KTe) and electron number density (ne) are measured at the applied voltage ranging from 400V to 700V, between the two electrodes, and pressure, inside the discharge tube, ranging from 0.013mbar to 0.070mbar. Our result showed that electron temperature (KTe) and electron number density (ne) increases with the pressure inside the discharge tube and applied voltage across the electrodes.